The Relation of Allergic Rhinitis Classification with IL-5 on The Aller-gic Rhinitis - Ismayani (Sumatera Medical Journal, 2019)
IL-5 is an important role cytokine on the RA. IL-5 has an important role on eosinophils. ARIA-WHO made classification of RA based on how long the clinical symptoms and the impact on quality of life. The aim of this study was to know the classification of RA with IL-5 on RA study. This study used a cross-sectional method with 39 samples. The examination of IL-5 used ELISA. The highest classification of RA was medium-severe persistent of 43.58% with the mean value IL-5 was 56.25 pg/ml. Based on the test of Kruskal Wallis, it was obtained p-value = 0.664. Conclusion: There was no significant relation between classification RA and IL-5.